Regional integration and south-south cooperation in health in Latin America and the Caribbean Integración regional y cooperación sur-sur en materia de salud en América Latina y el Carib - Alejandra Carrillo Roa; José Paranaguá de Santana (Pan American Health Organization, 2012)
This paper analyzes whether south-south cooperation is legitimately a recent practice or merely an improved version of previous regional integration processes in Latin America and the Caribbean. The authors reviewed and systematized the historic development of subregional integration processes in Latin America and the Caribbean and focused on health cooperation in the following contexts: the Central American Integration System, the Andean Community of Nations, the Caribbean Community, the Amazon Cooperation Treaty Organization, the Southern Common Market, and the Union of South American Nations. The study concludes that the conceptual and methodologic foundations of south-south cooperation in health were born from and nurtured by the processes of regional integration in Latin America and the Caribbean. This paper posits that regional political and economic integration initiatives bring potential benefits to the health sector and act as an important mechanism to develop south-south cooperation in this domain. The study recommends furthering this type of research to provide information that will allow national and multilateral agencies, or other stakeholders, to formulate and implement better policies for international health cooperation that target reducing inequities and promoting health and well-being for all people. Este artículo analiza si la cooperación sur-sur constituye legítimamente una práctica reciente o es solo una versión mejorada de los procesos anteriores de integración regional en América Latina y el Caribe. Los autores analizaron y sistematizaron el desarrollo histórico de los procesos de integración subregional en América Latina y el Caribe y se centraron en la cooperación en materia de salud en los siguientes contextos: el Sistema de Integración Centroamericana, la Comunidad Andina de Naciones, la Comunidad del Caribe, la Organización del Tratado de Cooperación Amazónica, el Mercado Común del Sur y la Unión de Naciones Suramericanas. El estudio concluye que las bases conceptuales y metodológicas ...